ANALISA HUKUM TERHADAP TINDAK PIDANA PENCABULAN ANAK - Radisman Saragih (to-ra, 2016)
Sexual abuse is a heinous act and barbarous, especially when sexual harassment occurs in a child under age whose minds are still innocent and do not know about as a result of the disaster that happened. Factors sexual abuse of children under age due to young children innocent and powerless, particularly when dealing with adults, especially parents, brother, uncle, grandfather, teacher or neighbor; the low morality and mentality of the perpetrators; experience of small actors who have been victims of sexual abuse during childhood so as to seek satisfaction performed on small children. That in order to prevent the crime of sexual abuse of children under the public is parents running the communication and emotional attachment to the child; parents give understanding to the children about their bodies and things that should not be done or dirabah by others of the body parts; the existence of coordination among law enforcement agencies on criminal acts of sexual abuse against minors and if convicted the perpetrators given severe sanctions, and if necessary an additional form of punishment gelding to sour people who commit criminal acts of sexual abuse and at the same be a threat to people who intend to do the same criminal offense